Genome-wide association studies reveal putative QTLs for physiological traits under contrasting phosphorous conditions in wheat (Triticum aestivum L.) - Dharmateja, Palaparthi; Yadav, Rajbir; Kumar, Manjeet; Babu, Prashanth; Jain, Neelu; Mandal, Pranab Kumar; Pandey, Rakesh; Shrivastava, Manoj; Gaikwad, Kiran B.; Bainsla, Naresh Kumar; Tomar, Vipin; Sugumar, S.; et al. (Frontiers in Genetics, 2022)
Genome-wide association (GWAS) study was conducted for phosphorous (P)-use responsive physiological traits in bread wheat at seedling stage with contrasting P regimes. A panel of 158 diverse advanced breeding lines and released varieties, and a set of 10800 highly informative single nucleotide polymorphism (SNP) markers were used to study marker-trait associations among eight shoot traits. Principle component analysis clearly separated the two environments along with the traits important for that environment indicating, thereby, separate breeding programme for each environment. Significant variations were observed for all the traits between genotypes and the contrasting phosphorus regimes along with moderately high broad sense heritability traits (0.50 to 0.73). Adoption of different trait association algorithms identified 38 unique under non-limiting P (NLP) and 45 QTLs for limiting P (LP) conditions for various shoot traits. Some of these QTLs were captured by all the three algorithms. Interestingly, a Q.iari.dt.sdw.1 on chromosome 1D was found to explain the significant amount of variations in three important physiological traits under NLP conditions, showing its involvement in number of important traits under optimal P conditions. Annotation of several genomic regions identified in this study against the expression atlas of wheat, revealed their co-localization in the chromosome regions harbouring essential pertinent genes for stress response and growth development processes in wheat. We identified the putative candidate genes Q.iari.dt.chl.1, Q.iari.dt.sdw.16, Q.iari.dt.sdw.9 and Q.iari.dt.tpc.1 which are potentially involved in mechanism regulating phosphorus use efficiency through improved P absorption due to improved root architectural traits and better mobilization such as sulfotransferase involved in postembryonic root development, WALLS ARE THIN1 (WAT1), a plant-specific protein that facilitates auxin export; lectin receptor-like kinase essentially involved in plant development, stress response during germination and lateral root development and F-box component of the SKP-Cullin-F box E3 ubiquitin ligase complex and strigolactone signal perception.. Our results thus provide an important insight in understanding genetic basis for improving PUE and can shape the future breeding programme by developing and integrating molecular markers for these deficult to score important traits.